2017
DOI: 10.1007/s00330-017-5156-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the histopathologic findings of intrahepatic cholangiocarcinoma: qualitative and quantitative assessment of diffusion-weighted imaging

Abstract: • ADC quantification was useful for predicting ICC tumour grade. • Infiltrative tumour morphology and size were associated with poorly differentiated ICCs. • ADC values depended more on ICC tumour grade than fibrosis content. • Ability to predict ICC tumour grade non-invasively could impact patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Signals on DWI images were determined as a) diffusely hyperintense, b) diffusely hypointense, c) target sign, or d) isointense. The target sign was described as peripheral diffusion restriction with central isointensity/hypointensity, which is believed to represent peripheral tumor growth and central fibrosis . Dynamic patterns of enhancement (DCE) were defined as A) persistent: the enhancement remained unmodified through all three phases; B) progressive: the intensity or range of enhancement progressively increased over time, centripetal enhancement was included; C) degressive (washin without washout): decreasing hyperintensity over time without hypointensity on portal or delayed phases; D) washin with washout: intense hyperintensity during the arterial phase followed by relative hypointensity on portal or delayed phases.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Signals on DWI images were determined as a) diffusely hyperintense, b) diffusely hypointense, c) target sign, or d) isointense. The target sign was described as peripheral diffusion restriction with central isointensity/hypointensity, which is believed to represent peripheral tumor growth and central fibrosis . Dynamic patterns of enhancement (DCE) were defined as A) persistent: the enhancement remained unmodified through all three phases; B) progressive: the intensity or range of enhancement progressively increased over time, centripetal enhancement was included; C) degressive (washin without washout): decreasing hyperintensity over time without hypointensity on portal or delayed phases; D) washin with washout: intense hyperintensity during the arterial phase followed by relative hypointensity on portal or delayed phases.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Lee et al reported that the degree of diffusion restriction in IMCC was an independent prognostic factors for overall survival . In addition, Lewis et al reported that the ADC value of IMCC was predictive of tumor grade . Therefore, we have reason to believe that DWI has more potential to assess ICC.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In a study with emphasis on diffusion-weighted imaging (DWI) measured with magnetic resonance imaging (MRI), the authors demonstrated that ICCs with > 1/3 diffusion restriction had more favorable histopathologic features and better clinical outcomes compared to those with < 1/3 diffusion restriction, as less diffusion restriction is believed to correlate with more fibrous stroma [16]. With regards to the apparent diffusion coefficient (ADC) quantification, it has been suggested that the ADCmean of ICC is significantly lower than that of the adjacent liver parenchyma, and that poorly differentiated tumors demonstrated a significantly lower ADCmean than well or moderately differentiated tumors [17,18]. Lastly, it is recognized that F-18 FDG PET/CT is an important diagnostic tool in staging of ICC.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the ADC mean value of two different components was 1.19 × 10 − 3 mm 2 /s (ICC component) and 1.95 × 10 − 3 mm 2 /s (sarcomatous component), respectively. Lower mean ADC value is associated with more aggressive histopathology and poorly differentiated ICCs [ 32 ]. The ADC value indicates that the ICC component has more malignant potential than the sarcomatous component.…”
Section: Resultsmentioning
confidence: 99%